The Car Resequencing Problem with Pull-Off Tables - Nils Boysen; Uli Golle; Franz Rothlauf (BuR - Business Research, 2011)
The car sequencing problem determines sequences of different car models launched down a mixed-model assembly line. To avoid work overloads of workforce, car sequencing restricts the maximum occurrence of labor-intensive options, e.g., a sunroof, by applying sequencing rules. We consider this problem in a resequencing context, where a given number of buffers (denoted as pull-off tables) is available for rearranging a stirred sequence. The problem is formalized and suited solution procedures are developed. A lower bound and a dominance rule are introduced which both reduce the running time of our graph approach. Finally, a real-world resequencing setting is investigated.
urn:nbn:de:0009-20-32115
Keywords: 650; mixed-model assembly line; car sequencing; resequencing; Fließfertigung; Mass Customization; Produktgestaltung; Kraftfahrzeugindustrie; Graphentheorie